Creative reconstructions of political imagery in an Instagram-based election campaign: implications for visual rhetorical literacy - Molek-Kozakowska, Katarzyna; Kampka, Agnieszka (Creativity Studies, 2021)
This article reviews literature on visual rhetoric in political campaigning and synthesizes several strands of current research devoted to the rhetorical potential of communicating with visuals in online environments. It uses rhetorical concepts of identification and manoeuvring, as well as the category of topos, to discuss the implications of an abductive analysis of a coded corpus of 1976 Instagram images posted during 2019 election to the European Parliament campaign in Poland. On this basis, the article offers recommendations related to the awareness of topoi in visual rhetoric to foster users’ creative inventory. In the context of increasingly strategically designed and creative online political communications, scholarship should offer guidance on how to parse images according to how they (mis)represent political reality to fit the purposes of elite communicators, and how to challenge them.